On the pure spinor heterotic superstring b ghost - Fleury, Thiago [UNESP] (Springer Nature, 2016)
Abstract: A simplified pure spinor superstring b ghost in a curved heterotic background was constructed recently. The b ghost is a composite operator and it is not holomorphic. However, it satisfies (Formula presented.) , where Q is the BRST charge. In this paper, we find a possible Ω.
Keywords: Superspaces; Superstrings and Heterotic Strings